Use v = 3 and y = 6 to determine if the expressions 3x + 2(x + 1) - 4 and 16 + 3v – v are equivalent. Which
statements are true? Check all that apply.
O The value of both expressions when v = 3 is 13.
0 The value of both expressions when u = 3 is 22.
The value of both expressions when u = 6 is 28.
The value of both expressions when v = 6 is 46.
0
O
The expressions are equivalent.
The expressions are not equivalent.

Respuesta :

Answer:

C and F.

Step-by-step explanation:

The value of both expressions when v = 3 is 13.

The value of both expressions when v = 3 is 22.

The value of both expressions when v = 6 is 28.

The value of both expressions when v = 6 is 46.

The expressions are equivalent.

The expressions are not equivalent.

Answer:

c f

Step-by-step explanation: